Rancang Bangun Digital Home Assistant Dengan Perintah Suara Menggunakan Raspberry Pi Dan Smart Phone - Isni Fachri Rizal; I Wayan Agus Arimbawa; Royana Afwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2018)
Digital home assistant is one part of smart home technology. The smart home is one of technology research that focuses on home automation, so the interaction between human and home becomes easier and more practical. One of the interactions that can be done is using voice commands. Currently, digital home assistant technology can be implemented with a variety of concepts and various tools. One of the tools that can be used is the smartphone. A smartphone is a communication tool that has a variety of tools to meet the needs of users, one of which is a tool offered by the Android operating system that is Google speech API. With google speech API we can build applications that can understand human speech. In order for home electronics devices to communicate with smartphones, use a microcontroller that is attached to the home electronics. Some microcontrollers that can be used are Raspberry Pi and Arduino. In this study, built a digital home assistant with voice commands using Raspberry Pi and smartphone. The built-in digital home assistant is used for lamp, TV and AC control. The Google speech API is used on smartphones for the process of translation of voice commands provided by users of the system. The results obtained for the control of lights, TV and air conditioning with voice commands using smartphones and Raspberry Pi is a system can run with 90% success and the average time of command execution reaches is 5.32 seconds.